Strategic positioning and creating competitive advantage in a challenging industry: The case study of Singapore airlines - Ta, Minh Thu (2009)
The competitive landscape of global airline industry has changed dramatically as the result of airline deregulation and globalization impacts. Arguably, the most viable change for traditional airlines is the increased price pressures due to fierce competition from low cost carriers (LCCs). The ‘no frills’ formula, which involves reduction in service and comfort levels, challenges the retaining of full service model and more generally, the model focusing on service quality. Furthermore, reduction in average profitability, instability in return rate of traditional airlines leads to urgent need for traditional airlines to change business model. This research gave serious attention to key factors that shape the competition in airline sector, with aims to identify what sustainable competitive advantage that conventional airlines should focus on. Drawing from extensive industry indicators and market information, it was found that demand for air travel is so diverse and there is potential for service differentiation. In deed, if implemented successfully, network carriers can earn superior profit. The research conducted comprehensive and in-depth analysis of Singapore airlines, a highly profitable and famous for its service excellence. It was argued that SIA’s consistent outperformance is the result of both effective cost management and premium service offers. The dissertation concludes that airlines, especially conventional carriers need to excel in both cost control and service quality if they are to survive and prosper. In order to achieve these seemingly exclusive strategies, internally coherent self-reinforcing business system is needed. Hyper service differentiation is the ultimate competitive advantage for airlines in this new phase of industry development.